Biomaterial applications of silk fibroin electrospun nanofibres - YÜKSELOĞLU, SEVHAN MÜGE; CANOĞLU, SUAT (ELSEVIER, 2015)
Electrospinning has been very interesting for the recent years and is used since 1994. Today, continuous ultra-fine fibres can be formed with the help of electrical forces to produce various polymer fibres at nanometre scale diameters. Here, it is aimed to discuss this process, for silk fibroin nanofibres and their applications. Silk can be varied in composition, structure and properties. Bombyx mori is one of the most studied silk which is widely used as a suture in biomaterial applications. This study focuses on a review of silk fibroin nanofibres and their biomaterial applications. Also, both electrospinning method, the selection of a solvent for the process and SF (silk fibroin) electrospun nanofibre fabrication methods are discussed. Additionally, some studies using SF as biomaterial methods are discussed for tissue engineering applications in this manuscript. It is noteworthy that SF fibres in biomaterials have increased over the last decade due to its excellent mechanical properties, water and thermal resistance, biodegradability and biocompatibility with a variety of end-use in the biomaterials. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Biomaterial; Silk; Fibroin; Electrospinning; Nanofibre; BOMBYX-MORI SILK; SCAFFOLDS; MEMBRANES; FIBER; CHITOSAN; BLEND; REGENERATION; ARCHITECTURE; PROTEINS; SURFACE